2019
DOI: 10.3389/fphys.2019.01202
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hits in Acute Pancreatitis: Components of Metabolic Syndrome Synergize Each Other’s Deteriorating Effects

Abstract: IntroductionThe incidence of acute pancreatitis (AP) and the prevalence of metabolic syndrome (MetS) are growing worldwide. Several studies have confirmed that obesity (OB), hyperlipidemia (HL), or diabetes mellitus (DM) can increase severity, mortality, and complications in AP. However, there is no comprehensive information on the independent or joint effect of MetS components on the outcome of AP. Our aims were (1) to understand whether the components of MetS have an independent effect on the outcome of AP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 41 publications
3
45
1
1
Order By: Relevance
“…In our study, though, the complications of AP were significantly higher in the MetS group than in the non-MetS group, but unlike the study mentioned, hypertension was not associated with an increase in AP severity based on the RAC and BISAP score. 17 In our study, increasing waist circumference, as an important indicator of obesity, was statistically significant associated with AP severity based on both criteria of the RAC and BISAP score (Tables 4-6). This result is consistent with the results of most studies suggesting that obesity has a negative impact on the AP process.…”
Section: Discussionsupporting
confidence: 52%
“…In our study, though, the complications of AP were significantly higher in the MetS group than in the non-MetS group, but unlike the study mentioned, hypertension was not associated with an increase in AP severity based on the RAC and BISAP score. 17 In our study, increasing waist circumference, as an important indicator of obesity, was statistically significant associated with AP severity based on both criteria of the RAC and BISAP score (Tables 4-6). This result is consistent with the results of most studies suggesting that obesity has a negative impact on the AP process.…”
Section: Discussionsupporting
confidence: 52%
“…Zeng et al [93] verified that hypertriglyceridemia was associated with local and systemic complications. Szentesi et al [84] verified that hypertriglyceridemia elevated the risk of severe AP.…”
Section: Hyperlipidemiamentioning
confidence: 98%
“…Few studies related metabolic syndrome with acute pancreatitis and their results are varied. However, a high prevalence of metabolic syndrome has been found in patients with AP and some studies associate this syndrome to severe forms of AP [82][83][84]. Mikolasevic et al [82] showed that patients with metabolic syndrome had a significantly higher incidence of moderately severe and severe AP in comparison to those without metabolic syndrome.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…According to the 2012 Atlanta classi cation, 24% patients met the diagnostic criteria of severe acute pancreatitis (SAP). 48.9% patients had recurrent AP (recurrence times: 2 [1,3]) and 36.1% patients were complicated with diabetes.…”
Section: Baseline and Clinical Characteristics Of Patients With Shtgpmentioning
confidence: 99%
“…Acute pancreatitis (AP) is an in ammatory disease of the pancreas with a worldwide incidence of cases per 100,000 per annum [1,2]. Metabolic syndrome was proved to be closely related to the development and/or severity of AP [3,4]. As one of the components of metabolic syndrome, severe hypertriglyceridemia (sHTG), de ned as a serum triglyceride (TG) level>11.3 mmol/L, is a common cause of AP [5,6].…”
Section: Introductionmentioning
confidence: 99%